Capital exports to less developed countries - Guth, Wilfried (Dordrecht-Holland : D. Reidel, 1963)
The book describes the novel elements in the world economic setting which explain the historically unprecedented phenomenon of large-scale government capital transfers to poor countries which have dominated the picture of foreign investment in these countries since the second World War. Decolonisation, the Cold War, the lesser appetite for imports of the United States as compared to the United Kingdom, the widespread use of exchange controls in poor countries, higher domestic levels of activity in advanced countries and a decreased readiness to take risks are adduced as reasons for the relatively low level of private capital flows to capital-hungry continents.
Includes index
Bibliography pp.157-161
usc 18/05/18
Loans
Keywords: Investments, Foreign; Economics; Capital; Developing countries